Nursing Home Referral Within the Veterans Health Administration: Practice Variation by Payment Source and Facility Type - Miller, Edward Alan (Res Aging, 2017)
Veterans enrolled within the Veterans Health Administration (VHA) of the U.S. Department of Veterans Affairs (VA) may receive nursing home (NH) care in VHA-operated Community Living Centers (CLCs), State Veterans Homes (SVHs), or community NHs, which may or may not be under contract with the VHA. This study examined VHA staff perceptions of how Veterans’ eligibility for VA and other payment impacts NH referrals within VA Medical Centers (VAMCs). Thirty-five semistructured interviews were performed with discharge planning and contracting staff from 12 VAMCs from around the country. VA staff highlights the preeminent role that VA priority status played in determining placement in VA-paid NH care. VHA staff reported that Veterans’ placement in a CLC, community NH, or SVH was contingent, in part, on potential payment source (VA, Medicare, Medicaid, and other) and anticipated length of stay. They also reported that variation in Veteran referral to VA-paid NH care across VAMCs derived, in part, from differences in local and regional policies and markets. Implications for NH referral within the VHA are drawn.